2014
DOI: 10.1186/1479-5868-11-33
|View full text |Cite
|
Sign up to set email alerts
|

Improving perceptions of healthy food affordability: results from a pilot intervention

Abstract: BackgroundDespite strong empirical support for the association between perceived food affordability and dietary intake amongst families with a lower socioeconomic position (SEP), there is limited evidence of the most effective strategies for promoting more positive perceptions of healthy food affordability among this group. This paper reports findings from a pilot intervention that aimed to improve perceptions of healthy food affordability amongst mothers.FindingsParticipants were 66 mothers who were the paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
17
2
Order By: Relevance
“…The perception that healthier foods are less affordable is frequently cited as a barrier to improving dietary habits ( 32 , 33 ) ; however, the current study suggests this is not the case when manipulating habitual intake under tightly controlled trial conditions and costing foods as consumed. Implementing similar dietary changes in priority groups (i.e.…”
Section: Discussioncontrasting
confidence: 66%
“…The perception that healthier foods are less affordable is frequently cited as a barrier to improving dietary habits ( 32 , 33 ) ; however, the current study suggests this is not the case when manipulating habitual intake under tightly controlled trial conditions and costing foods as consumed. Implementing similar dietary changes in priority groups (i.e.…”
Section: Discussioncontrasting
confidence: 66%
“…The budgeting component of the FOODcents curriculum focuses on challenging participants’ perceptions of the cost of healthy foods ( 24 ) . This approach reflects the recognized assumption that healthy foods are too expensive for those on limited budgets ( 39 ) . The costs of foods represented in each section of the healthy eating pyramid are compared during FOODcents courses, with real-life examples used to demonstrate that ‘Eat Most’ foods are the cheapest per kilogram, followed by ‘Eat Some’ and then ‘Eat Least’.…”
Section: Resultsmentioning
confidence: 99%
“…In Australia females of low SES reported that the perceived high cost of healthy food and a lack of time were important barriers for healthy eating ( 63 ) . Yet, it has been shown that healthy diets can be more affordable than current (less healthy) diets in Australia ( 64 ) and that an education-based intervention on food affordability improves perceptions of healthy food affordability in Australian mothers ( 65 ) . Reducing the perception of the high cost and time commitments associated with healthy eating may be particularly important for reducing DF intake.…”
Section: Discussionmentioning
confidence: 99%